P.076 Epidemiology of traumatic spinal cord injury patients in New Brunswick. (17th June 2016) - Chishti, YZ; Gaudet, D; O'Connell, C; Attabib, N
Abstract : Background: Characteristics of traumatic spinal cord injury (tSCI) patients admitted to the Saint John Regional Hospital and the Stan Cassidy Center for Rehabilitation from 2011 to 2014 were examined.Methods: Demographic, neurological and functional outcome data for 18 patients, who had consented to participate in a database for tSCI in Canada, was obtained.Results: The majority of patients were male (88.9%), with a mean age of 41. 33 ( SD= 17.17). The most common causes of tSCI were motor vehicle accidents (41.2%) and falls (29.4%). Cervical spine injuries (70.6%) and an ASIA impairment scale classification of D (38.9%) predominated. The median latency from injury to surgery was 22.67 hours. Functional independence Measure scores ( M= 64.17, SD= 25.84) indicated that motor/functional independence was impaired ( M= 32.44, SD= 19.15) relative to cognitive independence ( M= 31.83, SD= 4.07).Conclusions: The results suggest that characteristics of tSCI patients in New Brunswick are similar to the Canadian tSCI patient population. Emergency care appears to be delivered in a timely fashion. Both centers participate in research registries focused on collecting data related to tSCI, surgical interventions, and patient outcomes. Registries are valuable research tools that allow for an alternative way to examine the quality of care their patients receive.